Impact of Experiential Learning and Entrepreneurial Orientation on Student Start-up Business Performance with Social Network Moderation - Suharto Suharto; Vera Septi Andrini; Umi Hidayati; Erdyna Dwi Etika (Economics Education Department Universitas Negeri Semarang, 2025)
Entrepreneurship has become a key driver of economic growth and innovation. Universities play an important role in developing students' entrepreneurial competencies, but the factors influencing the success of students' start-up businesses must be better understood. This study aims to investigate the influence of experiential learning and entrepreneurial orientation on college students' start-up business performance and examine the moderating role of social networks. Using a quantitative research design, data were collected from a sample of 150 entrepreneurial students at an Indonesian university through a questionnaire. The data was analyzed using the Structural Equation Modeling (SEM) technique with SmartPLS. Results showed that experiential learning (β = 0.352, p < 0.001) and entrepreneurial orientation (β = 0.417, p < 0.001) positively and significantly influenced students' start-up business performance. The social network was found to moderate the relationship between entrepreneurial orientation and business performance (β = 0.183, p < 0.05). This study concludes that combining experiential learning, entrepreneurial mindset development, and social capital fostering is essential to nurturing successful young entrepreneurs. The findings provide valuable insights for universities in designing effective entrepreneurship education programs.